Vous êtes sur la page 1sur 6

# Indices, Logarithms and Surds

## Yue Kwok Choy

1 1 1 1 1
1. Prove that + + = +
1 + x a b + x a c 1 + x b c + x b a 1 + x c a + x c b 1 + x a b 1 + x b a

1 1

2. Given that x2 + x 2
= 3 , find the values of :

3 3

(a) x2 + x-2 (b) x2 + x 2

n 3
= 1 , find the possible values of n which satisfy the given equation.
2
3. If 7 2n

## 4. Find the values of x in each of the following equations :

x +1
(a) 9 43
x
+ 27 = 0
x 1 x +1
(b) 4 + 3 2 64 = 0

2 x + 3 y = 41
5. Solve the equations : x +2 y+ 2
2 + 3 = 209
1 1 1 1 1 1 1

(x 2 y 4
+ 2x 2 y 4 2)( x + 2x 2 y 4 + 2 y 2 )
6. Simplify
x 2 + 4y

7. Find two real values of k for which the equation log10 |x2 + 2kx| = 0 has a double root.

x x
8. Solve the equation : = 10 1
x log x

9. The quadratic equation 2x2 log a + (2x 1) log b = 0, where a and b are positive constants, has
non-zero equal roots. Express b in terms of a.

10. Let log x ab = log a x + log b x and ab 1. Show that log x a log x b = 1 .

8 in terms of a.

## 12. If y = a + bxn is satified by the values :

x 1 2 4
y 7 10 15
5
shown that n = log 2 and deduce the values of a and b .
3

## 13. Let log a c + log b c = 0 . Show that abc + 1 =ab + c

1
1
14. From the definition of a logarithm, prove that log a x = .
log x a

13
Hence, or otherwise, solve the equation : log x 8 + log 8 x = .
6

x y log b c log b a
15. If loga n = x and logc n = y where n 1, prove that = .
x + y log b c + log b a
Verify this result, without using calculators , when a = 4, b = 2, c = 8 and n = 4096 .

## 16. Prove from the definition of a logarithm that :

1 1
(a) + =1 ,
log a (ab) log b (ab )
(b) loga b logb c logc a = 1 , and deduce the value of log5 32 log4 7 log49 125 .

5 3
17. If x= , find the value of 8x x2 .
5+ 3

## 18. Express with rational denominators :

1
(a)
3+ 2 5
1
(b)
3 + 2 +1

19. Given that log2 (x 5y + 4) = 0 and log2 (x + 1) = 1 + 2 log2 y , find the values of x and y .

x2
20. Given that log9 x = p and log 3
y = q , express xy and as powers of 3.
y

a 3 + 2a 2 b + b 3 a
21. Find the value of when = 2 1 .
ab(a + 3b ) b

1 1 1
22. If a, b, x, y and z are numbers greater than 1 and ax = by = (ab)z , show that + = .
x y z

2
1 x b+c
1. =
1 + x a b + x a c x b+c + x c+ a + x a + b

x b+c x c+a x a +b
L.H.S. = + +
x b+c + x b + c x a b + x b + c x a c x c + a + x c + a x b c + x c + a x b a x a + b + x a + b x c a + x a + b x c b

## x b+c x c+a x a+b x b+c + x c+a + x a + b

= + + = =1
x b+c + x c+ a + x a + b x c+a + x a + b + x b+ c x c+a + x a + b + x b +c x b+ c + x c+a + x a + b

1 1 xb xa xa + xb
R.H.S. = + = + = =1 L.H.S. = R.H.S.
1 + x a b 1 + x b a x b + x a x a + x b x a + x b
1 1

2. (a) x2 + x 2
=3 . (1)

## (1)2 , x + 2 + x-1 = 9 , x + x-1 = 7 . (2)

2 2 -2 2 -2
(2) , x + 2 + x = 49, x + x = 47 . (3)
3 3
1 1 1
( )
3 3 1

(b) x +x 2 2
= x 2 + x 2 = x 2 + x 2 x 1 + x 1 = 3(7 1) = 18

n 3
=1 72n n 3
= 7 0 2n 2 n 3 = 0 (n + 1)(2n 3) = 0
2 2
3. 7 2n
3
n = 1,
2

4. (a) 9 x 4 3x +1 + 27 = 0 3x ( ) 2
( ) [ ][ ]
12 3x + 27 = 0 3x 3 3x 9 = 0 3x = 3 or 32

x=1 or 2

(b) 4 x 1 + 3 2 x +1 64 = 0 2 2 x 2 + 6 2 x 64 = 0 2x( ) 2
+ 24 2 x 256 = 0

[ ][
2 x 8 2 x + 32 = 0 2 x = 8 = 23 , ] 2 x + 32 = 0 is rejected.
x=3.
2 x + 3 y = 41 u + v = 41 u = 32 2 x = 2 5 x = 5
5. Put u = 2x, v = 3y, x +2 y
2 + 3 = 209 4u + 9 v = 209 v = 9 y = 2
y+ 2
3 = 3
2

1 1 1 1 1 1 1

+ 2x 2 y 4 2)( x + 2x 2 y 4 + 2 y 2 )
1 1
(x 2 y 4
6. E= . Let u = x2 , v = y4 , so that u2 = x, v4 = y .
x 2 + 4y

## (uv 1 + 2u 1 v 2)(u 2 + 2uv + 2v 2 ) (u 2 + 2v 2 2uv)(u 2 + 2uv + 2v 2 ) (u 2 + 2v 2 ) 2 (2uv) 2

= =
E=
u 4 + 4v 4 uv u 4 + 4v 4 uv u 4 + 4v 4 ( ) ( )
u 4 + 4v 4
1 1
1
= = x 2y 4
=
(
uv u + 4v
4 4
uv )

## 7. log10 |x2 + 2kx| = 0 |x2 + 2kx| = 100 = 1 x2 + 2kx = 1 x2 + 2kx 1 = 0

x2 + 2kx + 1 = 0 or x2 + 2kx 1 = 0
Since the given equation has double roots 1 = (2k)2 4(1)(1) = 0 or 2 = (2k)2 4(1)( 1) = 0
k = 1 ( 2 = 4k2 + 4 = 0 has no solution )

3
3
3 3
log x log x
= 1 log x log x = 1 (log x ) log x 1 = 0
x x 3
= 10 1 x 2 = 10 1 log x 2
2
8.
2
log x
x 2

## 2(log x ) 3 log x 2 = 0 (2 log x + 1)(log x 2 ) = 0

1
log x = or log x = 2
2

2
1
- 1
x = 10 2 or 10 2 x= or 100
10

9. 2x2 log a + (2x 1) log b = 0 or 2x2 log a + 2x log b log b = 0 has non-zero equal roots.
= 0 and 2log b 0
(2log b)2 4 (2log a) (log b) = 0 4log b (log b + 2 log a) = 0

## 10. log x ab = log x a + log x b . Let u = log x a , v = log x b .

u+v
(uv 1)(u + v ) = 0
1 1
Then log x ab = log a x + log b x u + v = + u+v=
u v uv
u+v=0 or uv = 1

## If u + v = 0 , then log x a + log x b = 0 , log x ab = 0 and ab = 1 . This contradicts to ab 1.

uv = 1
log x a log x b = 1 .

## log12 8 log12 2 3 3 log12 2 log12 2 log12 2 2 log12 (12 / 3)

11. log 8= = = = 6 =3 = 3
3
log12 3 log12 31/ 2 1 / 2 log12 3 log12 3 log12 3 log12 3

log 12 log12 3 1 a
= 3 12 = 3
log12 3 a

## 12. 7=a+b . (1) , 10 = a + b(2n) . (2) , 15 = a + b(4n) . (3)

n
(2) (1), 3 = b(2 1) . (3)
n n n n
(3) (2), 5 = b(4 2 ) = b2 (2 1) . (4)
5 5
(4)/(3), = 2n , n = log 2
3 3
From (3), 3 = b(5/3 1) b = 4.5
From (1), a = 2.5

## 13. log a c + log b c = 0

log c log c
+ =0
log c log a + log b(=0
)
log c log ab
=0
( )
log a log b log a log b log a log b

log c = 0 or log ab = 0 c = 1 or ab = 1 .

If c = 1, L.H.S. = ab + c = R.H.S.
If ab = 1, L.H.S. = c + 1 = R.H.S.

4
1
1 1
14. y = log a x ay = x a = xy log x a = y= .
y log x a

6(log 8 x ) 13(log 8 x ) + 6 = 0
13 1 13
log x 8 + log 8 x = + log 8 x =
2

6 log 8 x 6

( ) ( )
3 3 2 2
(2 log8 x 3)(3 log8 x 2) = 0
3 2
log8 x = , x = 8 2 ,8 3 x = 23 2 , 23 3
2 3
x = 16 2 ,4

log b n log b n

x y log a n log c n log b a log b c log b c log b a
15. = = = .
x + y log a n + log c n log b n log b n log b c + log b a
+
log b a log b c

## x y log 4 4096 log 8 4096 log 4 4 6 log 8 84 6 log 4 4 4 log 8 8 6 4 1

= = = = =
x + y log 4 4096 + log8 4096 log 4 4 6 + log 8 84 6 log 4 4 + 4 log 8 8 6 + 4 5
log b c log b a log 2 8 log 2 4 log 2 23 log 2 2 2 3 log 2 2 2 log 2 2 3 2 1
= = = = = . Result follows.
log b c + log b a log 2 8 + log 2 4 log 2 2 3 + log 2 2 2 3 log 2 2 + 2 log 2 2 3 + 2 5

## a = (ab) x , b = (ab) y ab = (ab ) x (ab ) y = (ab) x

1 1 1 1 1 1
+ 1 1
y + = 1 . Result follows.
x y

## (b) x = loga b, y = logb c z = logc a ax = b, by = c, cz = a.

Hence axyz = byz = cz = a xyz = 1. Result follows.
5 3
log5 32 log4 7 log49 125 = log5 2 log4 7 log49 5 = (5log5 2) (log4 7) (3log49 5)

## = 15 (log5 2) (log4 7) (log49 5) =

15
4
( )( )
log 5 2 2 log 4 7 2 (log 49 5) = (log 5 4 )(log 4 49 )(log 49 5)
15
4
3
=3
4

5 3
=
( 5 3) 2
5 2 15 + 3 8 2 15
17. x=
5+ 3 ( 5 + 3 )( 5 3 ) = 5 3 = 2 = 4 15

## (x 4)2 = 15, x2 8x + 16 = 15, 8x x2 = 1 .

1 3+ 2+ 5 3+ 2+ 5 3+ 2+ 5
= = =
18. (a)
3+ 2 5 ( 3+ 2 5 )( 3 + 2+ 5 ) ( 3 + 2) 5 2
2 6

=
6 3+( 2 + 5)
12
3 2 + 2 3 + 30
=
12

5
1 1+ 2 3 1+ 2 3 1+ 2 3
= = =
(b)
3 + 2 +1 (1 + )(
2 + 3 1+ 2 3 ) (1 + 2 ) 3 2
2 2

=
(
2 1+ 2 3)
4
2+ 2 6
=
4

## 19. log2 (x 5y + 4) = 0 x 5y + 4 = 20 = 1 x = 5y 3 . (1)

log2 (x + 1) = 1 + 2 log2 y log2 (x + 1) = log22 + log2 y2 = log2 2y2 x + 1 =2y2 . (2)
1
(1)(2), 5y 3 +1 = 2y2 2y2 5y + 2 = 0 y= ,2 . (3)
2

2 2

## 20. log9 x = p x = 9p = 32p

p
log 3
y = q y = 3 = 3q / 2

xy = 3 3 2p q / 2
,
x2 ( )
32 p 4 p
= q/2 = 3 2
2 q

y 3

3 2
a a
+ 2 + 1
a 3 + 2a 2 b + b 3 b b ( ) ( )
3
2 1 + 2 2 1 +1
2
( )( ) (
2 1 3 2 2 + 2 3 2 2 +1)
21.
ab(a + 3b )
=
a a
+ 3
=
( 2 1)([ 2 1) + 3] =
(3 2 2 ) + 3( 2 1)
b b

5 2 7 + 6 4 2 +1 2
= = =1.
2 2

z z

22. x y
a = b = (ab) z
a = (ab) x
and b = (ab) y

z z

## ab = (ab) (ab) = (ab) x

z z
+ z z 1 1 1
Multiply, we have, x y
y + =1 + = .
x y x y z